The effects of Entonox on implication of painless labor and delivery satisfaction rate among pregnant women - afsar Rezaeipour; fariba Idenloo; zohre Khakbazan; kazem Kazemnejad (Tehran University of Medical Sciences, 2007)
Background & Aim: Labor pain is regarded as one of the most intolerable pains which women experience during their life. Although there are many alternatives which can effect on person's response and perception to pain and suffering, the pain is felt especially more severely and longer by primogeniture. Annually thousands of selective cesarean operations are performed just because of delivery pain frightening as the main reason. The pain can produce diverse and unwanted effects on delivery procedure and mother-fetus condition. So finding a method to relieve the pain and suffering is one the policies intently considered by health care systems. The aim of present study is to determine the effect of Entonox on implication of painless labor and woman's satisfaction in a Hospital in Orumieh in 1385. Methods & Materials: This research is a single blind clinical trail. Samples were consisted of women (160 persons), in two groups (each group 80 persons), which selected randomly. The intervention group used Entonox and the control group inhaled Oxygen. All subjects were instructed to use Visual Analogue Scale (VAS) and to inhale gases correctly. Due to emergency need for caesarean operation 2 members of the intervention group and 3 ones from the control group leaved the study. Data gathering tool were consisted of data registration form, VAS scale, mother vital sign recorder, and fetus heart rate recorder. The data were analysed using descriptive (relative & absolute frequencies, mean, and standard deviation) and inferential statistics (t-test, Mann-Whitney U, Chi-squared, Kolmogrove-Smirnov test) by SPSS computer software. Results: According to the findings pain severity rate among the intervention group significantly was lower than the control group in the different hours of delivery procedure (P<0.001). Using Entonox made no effect on mother's vital signs, labor process, fetus heart rate, first and fifth minute Apgar and bleeding rate after delivery. Also it was shown that probable side effects of Entonox inhalation such as drowsiness and mouth stiffness were more common in the intervention group (P<0.001), but no significant difference was seen in other complications. Meanwhile delivery satisfaction rate was higher in the intervention members. Conclusion: It seems that Entonox inhalation might come in useful as an effective and safe method to alleviate labor pain and suffering along side with fewer likely risks for fetus and mother in clinical centers.   Background & Aim: Labor pain is regarded as one of the most intolerable pains which women experience during their life. Although there are many alternatives which can effect on person's response and perception to pain and suffering, the pain is felt especially more severely and longer by primogeniture. Annually thousands of selective cesarean operations are performed just because of delivery pain frightening as the main reason. The pain can produce diverse and unwanted effects on delivery procedure and mother-fetus condition. So finding a method to relieve the pain and suffering is one the policies intently considered by health care systems. The aim of present study is to determine the effect of Entonox on implication of painless labor and woman's satisfaction in a Hospital in Orumieh in 1385. Methods & Materials: This research is a single blind clinical trail. Samples were consisted of women (160 persons), in two groups (each group 80 persons), which selected randomly. The intervention group used Entonox and the control group inhaled Oxygen. All subjects were instructed to use Visual Analogue Scale (VAS) and to inhale gases correctly. Due to emergency need for caesarean operation 2 members of the intervention group and 3 ones from the control group leaved the study. Data gathering tool were consisted of data registration form, VAS scale, mother vital sign recorder, and fetus heart rate recorder. The data were analysed using descriptive (relative & absolute frequencies, mean, and standard deviation) and inferential statistics (t-test, Mann-Whitney U, Chi-squared, Kolmogrove-Smirnov test) by SPSS computer software. Results: According to the findings pain severity rate among the intervention group significantly was lower than the control group in the different hours of delivery procedure (P<0.001). Using Entonox made no effect on mother's vital signs, labor process, fetus heart rate, first and fifth minute Apgar and bleeding rate after delivery. Also it was shown that probable side effects of Entonox inhalation such as drowsiness and mouth stiffness were more common in the intervention group (P<0.001), but no significant difference was seen in other complications. Meanwhile delivery satisfaction rate was higher in the intervention members. Conclusion: It seems that Entonox inhalation might come in useful as an effective and safe method to alleviate labor pain and suffering along side with fewer likely risks for fetus and mother in clinical centers.